The effects of resilience on subjective stress response and salivary secretory immunoglobulin A in university students - Hisashi Mitsuishi; Shintaro Endo; Takayuki Ishiwata; Kazuo Oishi (Japanese Society of Physical Fitness and Sports Medicine, 2016)
We examined the effects of resilience on life stress by measuring subjective and physiological responses. Subjects were 32 college students who reported no remarkable subjective burden at the start of the study (initial period: T1), but some level of stressful burden 3 months later (second period: T2). Resilience levels were evaluated using the Bidimensional Resilience Scale (BRS), which measures innate and acquired resilience. The subjective stress level was assessed with the Stress Response Scale-18 (SRS-18). Saliva was also collected to measure the salivary secretory immunoglobulin A (sIgA) level. BRS was performed at T1, and SRS and saliva collection were administered at both T1 and T2. The subjects were divided into high- and low-resilience groups according to their median scores at T1. Additionally, the high-resilience group was classified as either high-innate resilience (HIR) or high-acquired resilience (HAR), and the low-resilience group as low-innate resilience (LIR) or low-acquired resilience (LAR), respectively, to reveal information in more detail. The depression-anxiety score for the SRS-18 in the low-resilience group was significantly higher than that in the high-resilience group at T2. The sIgA level of the high-resilience group was significantly higher than that of low-resilience group at T2. There were significant negative correlations between innate resilience and depression-anxiety, and total SRS-18 score; and negative correlations among acquired resilience and depression-anxiety, helplessness, total SRS-18 score, and sIgA level, respectively. These results suggested that the stress response in low-innate and acquired resilience differs depending on the length of time elapsed with stress, because low-innate and acquired resilience causes higher susceptibility to "depression-anxiety" as a psychological stress response factor. On the other hand, higher acquired resilience improved immune function in the presence of subjective burden.